Utilization of Generic Consumer Modeling in Planning and Optimization of District Heating and Cooling Systems - Atta, Khalid; Birk, Wolfgang (Luleå tekniska universitet, Signaler och system, 2018)
District heating and cooling (DHC) networks are large scale complex systems which aregenerally difficult to operate and optimize. The large thermal inertia in the systems leadsto long reaction times on changes at the consumer side, which means that forecasting ofconsumer behaviour is a needed tool for efficient operation. Within the European Unionmany major research project target the energy reduction on the consumption side and peakload management while maintaining customer satisfaction.The optimal operation of a DHC network can therefore be considered as an interestingarea of investigation due to a number of aspects, like (i) the vast amount of the energy that is distributed by these networks, (ii) the demand to provide a better quality of services by the operators of these networks, and (iii) compliance with new environmental regulations. In this presentation, we discuss a possible conceptual method that utilizes a simpliedstatic model of different types of consumers in the network to design a decision supportsystem that will guide the operators of the DHC network to optimally operate the networkwith different operational scenarios that include but not limited to: (i) energy consumptionminimization, (ii) economic operation, (iii) peak load reduction/shifting, and (iv) environmentally friendly operation. In its current form, the operator will be informed, while in thefuture these actions could be fully automated in a closed loop context.The DHC network in Luleå, Sweden will be used as a test case which represents a typicalmedium size network. The case has a number of properties which motivate its study likee.g. the distributed generation possibilities, the geographical distribution of the consumers,and the different types of consumers in the area. The presentation will be concluded with anoutlook on future tracks of research and development